A technique for reduction of mutual coupling by steering surface wave propagation. Issue 5 (27th January 2020) - Ghosh, Jeet; Mitra, Debasis
Abstract: In this article, we present an efficient approach to reduce mutual coupling in a planar slot antenna array by using high refractive index metamaterial. The metamaterial structure is employed to steer the propagation of the surface wave. For this purpose, array of complementary slot coupled split‐ring resonator structures are designed on the two sides of the slot array. The proposed configuration is fabricated and both simulation and measurement results confirm that an average of 10 dB improvements in isolation level is achieved throughout the wide operating bandwidth. Moreover, due to the implementation of the complementary metamaterial structure, the proposed configuration becomes planar and easy to fabricate.